Konsepsi Islam Tentang Manusia Dan Implikasinya Pada Pendidikan - Khairuddin Khairuddin (Jurnal Edukasi, 2022)
God affirms that man is at the top of his creation, with a degree of perfection and uniqueness that is superior to all other creatures. (QS.At-Tin:4). But God warned him that he was not yet perfected and that he had to struggle to be perfected. (QS.Asy-Syams:7-10). This perfecting process is possible because the human being is in essence philosophical, intellectual, and intelligent, plus the coming of the apostles of the Lord, bringing the Scriptures as guidance to mankind's life. (QS.An-Nisa:174). It will not be accomplished if man does not use his understanding and does not follow the guidance of God. Education is simply a process of humanizing man; "man is the core of the educational process", that is, man is the nucleus of an educational procedure. It shows that human beings are both objects and perpetrators of education. Therefore, the formulation and implementation of education must always be based on the concept of human rights. The potential of human reason is capable of producing science, which must be cultivated and developed in an optimal and integrated way through the educational process. He is the God of the earth, and he is the Lord of all things.